CONSUMER VALUATION OF GREEN PRODUCTS: INTERPLAY BETWEEN MARKETING CLAIMS, CERTIFICATION, AND BUYING INTENTIONS - N.Shah, Sheetal; Deshmukh, Dr. Meena (ShodhKosh: Journal of Visual and Performing Arts, 2024)
In the age of the rising environmental awareness, green products have been a subject of much attention of the consumer as well as marketing globally. The given research paper examines the role of both marketing claims and third party certifications and their effect on consumer buy-intentions related to green products. Although environmental marketing and eco-labels have been common tools used to transformed consumer behaviors, they are highly functional based on how consumers perceive them, validity of advertisement/claims and trustworthiness of certifications. The purpose of this study is to evaluate the spread of the consumers value of green products dues to the faithfulness of environmental suggestions and availability of officially recognized affirmations. The proposed study will measure the impacts of these elements on the willingness to pay, purchase intentions, and general trust in the green brands with the help of systematic questionnaire and the following analysis based on statistical methods. The results have shown that marketing claims are capable of increasing the knowledge but their importance on purchasing behavior is extremely reinforced in case they are accompanied by credible certifications. In addition, by the presence of emotional appeal and fact credibility, consumers exhibit an elevated level of valuation of the green products. The paper identifies the need to be transparent, have regulatory authority, as well as having uniform brand messaging to practice sustainable consumption. Marketers, policymakers and certification bodies can use this knowledge to make informed recommendations of ways to enhance genuine green marketing activities and uptake of products/ services that protect the environment.